Use complete the square and identify the conic.

X^2+y^2+4x-6y+1=0

A. (X-2)^2+(y+3)^2=2 square root 3
B. (X+2)^2+(y-3)^2=12

1 answer

To complete the square for this equation, we need to rewrite it as:

(X^2 + 4x) + (y^2 - 6y) + 1 = 0
(X^2 + 4x + 4) - 4 + (y^2 - 6y + 9) - 9 + 1 = 0
(X + 2)^2 - 4 + (y - 3)^2 - 9 + 1 = 0
(X + 2)^2 + (y - 3)^2 - 12 = 0

As we can see, by completing the square, we get the conic in the form (X + h)^2 + (y + k)^2 = r^2, which represents a circle.

Therefore, the correct answer is B. (X + 2)^2 + (y - 3)^2 = 12.
Similar Questions
  1. Use complete the square and identify the conic.X^2+y^2+4x-6y+1=0 A. (X-2)^2+(y+3)^2=2 square root 3 B. (X+2)^2+(y-3)^2=12
    1. answers icon 1 answer
  2. Add and Subtract Radicals Quick CheckMath 8 Q2 (Pre-Algebra) / Roots and Irrational Numbers add 3 square root 21 + 7 square root
    1. answers icon 1 answer
    1. answers icon 11 answers
  3. 1) Which of these is a rational number?a. Pi b. Square root 3 ****** c. Square root 2 d. 1.3 (the # 3 has a line at the top) 2)
    1. answers icon 44 answers
more similar questions